Efficacy and Safety of Mitoxantrone Hydrochloride Injection for Tracing Axillary Sentinel Nodes in Breast Cancer: A Self-Controlled Clinical Trial - Jiao, Dechuang; Yang, Benlong; Chen, Jiajian; Wang, Chunjian; Jin, Lidan; Zhao, Wenhe; Gao, Xueqiang; Wang, Haibo; Li, Jun; Zhao, Haidong; Wu, Di; Fan, Zhimin; et al. (Frontiers in Oncology, 2022)
Background Mitoxantrone hydrochloride injection for tracing (MHI), a new strategy to identify lymph nodes, has not been tested for axillary node staging in breast cancer. This multicenter, self-controlled, non-inferiority trial aimed to evaluate MHI’s efficacy and safety in sentinel lymph node biopsy (SLNB). Methods The trial was conducted across seven hospitals from December 2019 to December 2020. Patients with early-stage breast cancer received MHI and technetium-99m (99mTc) during the surgery. Sentinel node detection rates were compared between MHI and 99mTc to evaluate non-inferiority and concordance. Non-inferiority was valid if the lower limit of the 95% CI of sentinel node relative detection rate difference was ≥−5%. Results SLN relative detection rate of MHI was 97.31% (362/372). Of the SLNs, 79.69% (871/1093) were co-detected by both tracers. Of the patients, 4.13% (16/387) had adverse events and recovered during the follow-up. Conclusions MHI is a lymphatic tracer with comparable efficacy to radionuclides and can be used alone or in combination with radioactive substances for SLNB. Clinical Trial Registration http://www.chinadrugtrials.org.cn, CTR20192435.